CHALLENGES OF WASTE RECYCLING IN THE DEVELOPMENT OF A GREEN ECONOMY - Zulfakarova , Liliya; Tuychieva , Nodira (Effective scientific journals, 2025)
The transition toward a green economy places increasing emphasis on sustainable waste management and recycling systems. Selecting effective waste management strategies is crucial for minimizing environmental impacts, conserving natural resources, and generating socio-economic benefits for local communities. Decision-making in this field depends on multiple factors, including the type and volume of waste generated, available technologies and financial resources, existing and future policy frameworks, and environmental, social, and economic considerations. This study analyzes key challenges associated with waste recycling within the framework of green economic development. By comparing international policy approaches and technological solutions, including waste prevention, recycling, waste-to-energy systems, and anaerobic digestion, the paper highlights their relative effectiveness in achieving sustainability goals. The findings underline the importance of adopting a territorially adapted, integrated waste management strategy aligned with circular economy principles.